Le logiciel AVAA Toolkit : de nouvelles possibilités pour les données audiovisuelles annotées - Clotilde George; Charles George (Humanités Numériques)
In this article we present the AVAA Toolkit, a software dedicated to the exploration and analysis of annotated audiovisual data corpus. Developed within the framework of the language sciences, it is conceived as a complement to the annotation software used in digital humanities, such as Elan, Clan, Advene or Celluloid. Its main function is to enable the exploration of annotation data together with the audiovisual data to which they are linked, as is usual in text mining. Acting as an interface between annotation files, media files and the analyst, it produces data visualisations of different forms according to the needs of the analysis: list, table, concordances and various graphs.